PENERAPAN PEMBATASAN YUDISIAL (JUDICIAL RESTRAINT) BAGI PELAKU LGBT ( STUDI KASUS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-XIV/2016) - Widyawati Boediningsih; Evan Wijaya (Jurnal HUKUM BISNIS, 2019)
The existence of the Constitutional Court as a constitutional enforcement state institution is required to conduct judicial review of the Constitution State Law. In carrying out its duties and obligations acting in judicial activity as a positive legislator or performing judicial restrictions as a negative legislator.Lesbian, Gay, Bisexual and transgender hereafter abbreviated LGBT is one interesting phenomenon to be studied in terms of juridical. Legal certainty is needed in the solution of the LGBT case that has been rampant in the community